The Improvisational Situation (Itinera, 2015)
Some manuscripts of Maurice Merleau-Ponty are the core of the investigation about the improvisation pursued in this essay, an investigation within the domain of the philosophical interrogation about music.  Merleau-Ponty’s manuscripts are brought into contact with Marcel Proust’s lectures with the aim of going over the construction of the “concept of improvisation” and of reflecting on the following questions: in the experience of improvisation, is just as necessary to recognize the emotional profile as the cognitive profile? What place does the improvisation occupy in musical experience?